2017
DOI: 10.3126/acclm.v2i2.15590
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum uric acid and triglycerides level in the patients with Type II Diabetes Mellitus- a Nepalese case control study

Abstract: BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…52 Similar findings have been reported by different previous studies from Nepal. [53][54][55] This also highlights the need of interventions for prevention and control of several of these metabolic risk factors such as dyslipidaemia so as to achieve DM control in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…52 Similar findings have been reported by different previous studies from Nepal. [53][54][55] This also highlights the need of interventions for prevention and control of several of these metabolic risk factors such as dyslipidaemia so as to achieve DM control in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in Nepal reported the prevalence rate to be 28%. 21 Similarly a study conducted in Nigeria reported the prevalence rate to be 25%. Likewise, hyperuricemia in DM is also shown by other various studies.…”
Section: Discussionmentioning
confidence: 97%
“…8,9 A study from Nepal stated SUA was higher in patients with diabetes than in without diabetes. 10 Since the association of UA in patients without diabetes and with diabetes is not consistent, studies are required to know the actual trend of SUA in healthy and diabetic individuals. Although, there are some studies on the relationship between SUA and diabetes from different parts of the world, there are very few studies in Nepal.…”
Section: Introductionmentioning
confidence: 99%